In Good Company: Comments (American Journal of Islam and Society, 2018)
When I first walked into the living quarters of Begum Noor Jahan ZareefThanawi (1931-2017) in Karachi, I was fatigued from jetlag and notexpecting much to come of the meeting except polite verbal exchanges.But as I absorbed the functionality of every item in the sparsely furnishedroom, and the immense level of spiritual focus she carried within her frail(though still somehow strong!) physical frame, I realized I was sitting in thecompany of no ordinary woman. It was about Begum Zareef that Dr. ‘Abdal-Hayy ‘Arifi—one-time nāẓim of Dar al-‘Ulum Karachi and spiritual successorto Ashraf ‘Ali Thanawi—had remarked, “If we gave khilāfat (spiritualsuccessorship) to women, we would have given it to her.” Though not givenpermission to take spiritual disciples, her sheikh had given her a generalallowance to teach the religious sciences to women. She taught Qur’anicexegesis (tafsīr) for decades out of her home; wrote numerous pamphletson spirituality and religious practice; and published a volume on the legalrulings of Hajj, with a special focus on related women’s issues.If Begum Zareef were asked what was the secret that persuaded hersheikh to give her such a wide allowance to teach, I know her answer wouldbe the pious company (of her sheikh and others) that she kept throughouther life. As Ashraf ‘Ali Thanawi clarifies in Fawāʾid al-ṣuḥba, his famouslecture cited by Darakhshan Khan, it was the ṣuḥba (company) they’d keptthat made the Companions (Ṣaḥāba) who they were. Were it not for thefact that they had sat with the Messenger of God, they would not have attainedtheir otherwise unattainable spiritual and religious rank, and theywould not be seen as a necessary source of religious knowledge for all Muslimswho came after them. In my own book,1 I argue that ṣuḥba, in fact,lies at the spiritual center of Sunni Islam. For one to be a “real Sunni,” onedoes not merely have to accept the probity of every one of the Ṣaḥāba; onemust also accept that the preservation and continuation of true religious ...